Inactivation of tyrosinase photoinduced by pterin - Dantola, Maria Laura (2012)
Tyrosinase catalyzes in mammals the first and rate-limiting step in the biosynthesis of the melanin, the main pigment of the skin. Pterins, heterocyclic compounds able to photoinduce oxidation of DNA and its components, accumulate in the skin of patients suffering from vitiligo, a chronic depigmentation disorder in which the protection against UV radiation fails due to the lack of melanin. Aqueous solutions of tyrosinase were exposed to UV-A irradiation (350. nm) in the presence of pterin, the parent compound of oxidized pterins, under different experimental conditions. The enzyme activity in the irradiated solutions was determined by spectrophotometry and HPLC. In this work, we present data that demonstrate unequivocally that the enzyme is photoinactivated by pterin. The mechanism of the photosensitized process involves an electron transfer from tyrosinase to the triplet excited state of pterin, formed after UV-A excitation of pterin. The biological implications of the results are discussed.